2017
DOI: 10.1108/ejtd-08-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Organizational strategic learning capability: exploring the dimensions

Abstract: How to build and enhance the strategic learning capability of an organization becomes crucial to both research and practice. This study was designed to conceptualize strategic learning capability by translating and interpreting the related literature to develop empirical dimensions that could be tested and used in a survey instrument. The resulting survey instrument included fifty-nine items that were developed through a review of the literature, a brainstorming session of HRD practitioners, and communications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…It guides, train and educate organizational workers about the methods and techniques used to achieve organizational goals (Hotho et al., 2015). It plays vital role in developing learning organizations, by providing a complete map and model of working, keep the work force focused, therefore chance of error remains low and workers modify their pattern of work against the standard manuals, formats and model provided by organization (Moon et al., 2017). Strategic Cognition (SC) is a cognitive process of scanning, formulating, sense-making, decision making and implementing policies and play role in the cognitive construction of the organization (Kazmi and Naaranoja, 2015).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…It guides, train and educate organizational workers about the methods and techniques used to achieve organizational goals (Hotho et al., 2015). It plays vital role in developing learning organizations, by providing a complete map and model of working, keep the work force focused, therefore chance of error remains low and workers modify their pattern of work against the standard manuals, formats and model provided by organization (Moon et al., 2017). Strategic Cognition (SC) is a cognitive process of scanning, formulating, sense-making, decision making and implementing policies and play role in the cognitive construction of the organization (Kazmi and Naaranoja, 2015).…”
Section: Theorymentioning
confidence: 99%
“…Organizational cognition is a process or a set of processes that subsume attention, knowledge organization, decision-making and problem-solving. These processes are supported by organizational goals, environmental demands, threats and opportunities (Moon et al., 2017; Gino and Staats, 2015). It has been found that the most influencing cognitive factors of cognitive prospective are knowledge workers, leadership style and role, employees empowerment, organizational culture, organizational structure, organizational strategy, performance measurement system, training and development (Alalwan et al., 2016; Adcock, 2012; Coetzer et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Because knowledge cannot exist separately from the person who possesses it, organizational knowledge creation should be studied in terms of the intersubjectivity that emerges from members' interactions and sensemaking activities (J. S. Brown & Duguid, ). Organizational sensemaking involves creating organizational knowledge based on individuals' interpretations of their environment (Colville, Brown, & Pye, ; Maitlis & Christianson, ; Moon, Ruona, & Valentine, ). Organizational knowledge generated by sensemaking remains in the organization, even if not consciously recognized by individuals (Lien, Hung, & McLean, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Organizations with dynamic capabilities can integrate, build and reconfigure internal and external competences to address rapidly changing environments (Teece et al, 1997, p. 516). Moon et al (2014) define strategic learning capability as the organization's capacity to retool rapidly to create and execute new 629 Strategic learning capability strategy through learning at the individual and system levels in response to changes and uncertainties in complex environments.…”
Section: Strategic Learningmentioning
confidence: 99%